Transcutaneous electrical nerve stimulation, pregabalin and their combination in patients with painful diabetic neuropathy - Moharić, Metka (Zdravniški vestnik, 2009)
Background Peripheral neuropathy is a common complication of diabetes, wherebypain control is the most difficult issue. The outcomes of existing treatment options are far from satisfactory and the results of studies comparing them are indecisive. Hence, we aimed at comparing the effect of treating pain with transcutaneous electrical nerve stimulation (TENS), pregabalin and their combination in patients with painful diabetic neuropathy (PDN), including the quality-of-life aspect. Methods A randomized clinical trial was planned with 69 PDN patients divided into three equally sized groupsreceiving TENS, pregabalin or combined treatment. Because of early dropouts from the pregabalin and combination group due to side effects, randomization was abandoned during recruitment phase and all remaining patients were assigned to TENS, resulting in group sizes of 46, 5 and 14,d of treatment. Results Observed treatment effects did not differ between the groups. Statistically significant and clinically meaningful reduction of average and worst pain was achieved. Patients rated their quality of life better especially in the bodily pain domain of Short Form-36. One month post treatment, all observed effects were still present. Pain reduction correlated mainly with improvement of physical functioning domain. Conclusions Since TENSdid not differ in efficacy from pregabalin and combined treatment, and does not have side effects, it appears to be a viable addition or even alternative to other analgesic modalities in PDN. respectively. Assessments for pain relief and quality of life were performed at baseline, at the end of three-week treatment, and one moth after
Keywords: Bolečina; Calcium Channel Blockers; Controlled Clinical Trials; Diabetic Neuropathies; diabetična nevropatija; Diabetične nevropatije; Drug Therapy; električno draženje; Kalcijev kanalček, blokatorji; Kontrolirane, klinične raziskave; Kvaliteta življenja; Pain; Quality Of Life; Therapy; Transcutaneous Electric Nerve Stimulation; Transkutano, električno draženje živca; Treatment Outcome; Zdravljenje, izid